Method for enhancing perovskite LED performance based on precious metal nanostructure
By integrating precious metal nanoparticles on the metal top electrode of the perovskite LED device to form a self-assembled antenna, the problem of low external quantum efficiency and low optical output coupling efficiency of perovskite LED devices is solved, and higher optical output coupling and external quantum efficiency are achieved, extending the half-life and life of the device.
Patent Information
- Application Number
- CN202411514614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-11
AI Technical Summary
The external quantum efficiency and light output coupling efficiency of perovskite LEDs are low, resulting in shortening of device half-life and thermal aging problems, affecting device stability and life.
By integrating precious metal nanoparticles on the metal top electrode of the perovskite LED device, a self-assembled antenna is formed to regulate the device's optical output coupling efficiency and external quantum efficiency.
Effectively reduce plasmon loss, enhance optical output coupling, improve external quantum efficiency, extend device half-life, and improve stability and life.
Smart Images

Figure CN119604131A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of optical technology, and in particular to a method for enhancing the performance of perovskite LEDs with precious metal nanostructures. Background Art
[0002] Perovskite light-emitting diodes (LEDs) have attracted much attention in the field of lighting and display research due to their high photoluminescence quantum efficiency (PLQE) and good carrier transport performance. The performance of perovskite LEDs is mainly defined by two key parameters: external quantum efficiency (EQE), which is calculated as the product of PLQE, carrier injection efficiency and outcoupling efficiency) and device half-life (T 50 , which is the time required for EQE to drop to half of its initial value). Through careful material design, both the PLQE and carrier injection efficiency of perovskite LEDs can reach 100%. As a result, the outcoupling efficiency becomes a limiting factor for further improving the EQE. Light output management involves the process of radiation from the emission layer (EML) to the far field, however, more than half of these photons are still trapped at the interface of the multilayer structure. In addition, the trapped photons may also cause thermal aging inside the device and even shorten the half-life of the device. To enhance the outcoupling of light, nanodome-shaped substrates, microcavities, and moth-eye structures have been integrated into perovskite LED devices, which greatly reduces the number of photons trapped at the interface due to dielectric differences. Plasmon losses in metal electrode interfaces, although theoretically predicted to be mainly used to explain the photon trapping phenomenon, have hardly been studied in depth in solving the outcoupling problem. Summary of the invention
[0003] The present invention utilizes a method based on precious metal nanostructures to regulate the external quantum efficiency, light output coupling efficiency, half-life, thermal aging, luminescence wavelength and other properties of the device to solve the problems mentioned in the above background technology.
[0004] In order to achieve the above object, the solution of the present invention is: a method for enhancing the performance of perovskite LED based on precious metal nanostructures, comprising the following steps:
[0005] Step 1: Depositing a bottom electrode using a thermal evaporation system;
[0006] Step 2, spin coating the hole transport layer using a spin coater;
[0007] Step 3, preparing a perovskite precursor solution in a nitrogen glove box (O2≤1ppm, H2O≤1ppm);
[0008] Step 4, spin coating the perovskite film using a spin coater;
[0009] Step 5: Depositing an electron transport layer using a thermal evaporation system;
[0010] Step 6: Depositing a metal top electrode using a thermal evaporation system;
[0011] Step 7: Integrate precious metal nanoparticles with perovskite LEDs.
[0012] Furthermore, step 1 is specifically as follows:
[0013] A substrate of a certain size was selected, wiped clean with ethanol, and then cleaned with ultrapure water, acetone, and ethanol by ultrasonic cleaning for 15 minutes, and then dried with nitrogen. After drying, a thermal evaporation system was used to evaporate an adhesion layer with a thickness of a at a rate A, and then a noble metal layer with a thickness of b at a rate B, and then a noble metal layer with a thickness of c at a rate C as the bottom electrode.
[0014] Furthermore, step 2 is specifically as follows:
[0015] The evaporated substrate is treated in a plasma cleaning machine for a time d to enhance the surface hydrophilicity and remove organic impurities. The hole transport layer solution is spin-coated on the evaporated substrate at a rotation speed E in air for a spin coating time e, and annealed at a temperature F in air for a time f to prepare a hole transport layer.
[0016] Furthermore, step 3 is specifically as follows:
[0017] Lead halide, halide salt and small molecule additive are added to the solvent, the temperature of A1 is maintained, and the mixture is stirred at a certain speed B1 for a certain time T1. The solution is then filtered through a 0.45 μm polytetrafluoroethylene filter to obtain a clear and transparent precursor solution.
[0018] Furthermore, step 4 is specifically as follows:
[0019] The substrate obtained in step 2 is also transferred to a nitrogen-filled glove box, and then the perovskite precursor solution prepared in step 3 is spin-coated on the hole transport layer film at a certain rotation speed B2 for a spin coating time of T2. It is then placed on a heating plate and heated at a certain temperature A2 for a certain time T3 to obtain a perovskite film.
[0020] Furthermore, step 5 is specifically as follows:
[0021] After the perovskite film was prepared, the substrate was transferred to a high vacuum deposition system (vacuum pressure < 4 × 10 -4 The electron transport layer with a thickness of i is evaporated at a rate i using a shadow mask by thermal evaporation.
[0022] Furthermore, step 6 is specifically as follows:
[0023] After depositing the electron transport layer, a noble metal layer is deposited by thermal evaporation using a shadow mask. A noble metal layer with a thickness of j is evaporated at a rate J, and then a noble metal layer with a thickness of k is evaporated at a rate K to serve as a top electrode.
[0024] Furthermore, step 7 is specifically as follows:
[0025] In a nitrogen environment, a solution of gold nanoparticles was first evenly drop-coated onto the polydimethylsiloxane (PDMS) material and dried naturally; then, the side of the polydimethylsiloxane (PDMS) with the noble metal nanoparticles was adhered to the surface of the perovskite LED device (metal top electrode); finally, the polydimethylsiloxane (PDMS) was mechanically separated from the device.
[0026] Furthermore, in step 1,
[0027] The substrate can be one of glass, iron plate, steel plate, aluminum plate, wood chip, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and the substrate size is 100-1000mm 2 The materials of the adhesion layer are Cr, Cu, Zr, and W, and the rate A is The thickness a is 3-8 nm. The material of the bottom electrode metal layer includes but is not limited to precious metals such as gold, silver, and aluminum. The rate B is The thickness b is 2-7nm, and the rate C is The thickness c is 60-120 nm.
[0028] Furthermore, in step 2,
[0029] The hole transport layer solution can be an organic solution or an inorganic solution. The organic solution includes poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS), poly(3-hexylthiophene-2,5-diyl) (P3HT), poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)] (TFB), [bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly[[ 4,8-Bis[(2-ethylhexyl)oxy]-benzo[1,2-B:4,5-B']dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thiophene[3,4-b]thiophene] (PTBT), poly[bis(4-phenyl)(4-butylphenyl)amine] (Poly-TPD), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9, 9'-Spirobifluorene (Spiro-OMeTAD), poly (9-vinyl carbazole) (PVK), polyvinyl pyrrolidone (PVP) or other organic solutions; inorganic solutions are nickel oxide (NiO), vanadium pentoxide (V2O5), tungsten oxide (WO), cuprous oxide (Cu2O), cuprous thiocyanate (CuSCN), lithium fluoride (LiF) or other inorganic solutions. The hole transport layer solution can be a solution that can be used directly after purchase, or it can be a solution prepared by purchasing powder with other solvents. The hole transport layer can be a single-layer film after spin coating of a hole transport layer solution, or it can be a multi-layer film composed of several hole transport layer solutions spin coated separately. The time d is 5-20min, the rotation speed is 1000-9000rmp, the time e is 20-150s, the temperature F is 60-300℃, and the time f is 3-20min.
[0030] Furthermore, in step 3,
[0031] The lead halide is one or more of lead iodide (PbI2), lead bromide (PbBr2), and lead chloride (PbCl2); the halide salt is p-FPEABr, formamidine bromide, lithium bromide, cesium iodide (CsI), cesium bromide (CsBr), cesium chloride (CsCl), methylammonium iodide, methylammonium bromide, methylammonium chloride, methylammonium iodide, methylammonium bromide, methylammonium chloride, formamidine hydroiodide, formamidine hydrobromide, formamidine hydrochloride, phenethylammonium iodide, phenethylammonium One or more of phenylamine bromide (PEABr), phenethylammonium chloride, zinc chloride, strontium bromide (SrBr2), calcium bromide (CaBr2), magnesium bromide (MgBr2), strontium iodide (SrI2), magnesium iodide (MgI2), calcium iodide (CaI2), strontium chloride (SrCl2), calcium chloride (CaCl2), and magnesium chloride (MgCl2); the small molecule additive is dicyclohexane-18-crown-6, 5-aminopentanoic acid (C5H 11NO2), 2-aminobenzophenone-2'-carboxylic acid (C 14 H 11 NO3), 2,2-iminodibenzoic acid (HN(C6H4CO2H)2), 3-aminopropionic acid (C3H7NO2), 4-aminobutyric acid (NH2(CH2)3COOH), 5-aminohexanoic acid, 6-aminoheptanoic acid, 4-amino-3-hydroxybutyric acid (C4H9NO3), 2-aminocyclopentanecarboxylic acid (C6H 11 NO2), 3-aminocyclohexanecarboxylic acid (C7H 13 NO2), 4-aminophenylacetic acid (C8H9NO2), 3-aminophenylpropionic acid (C9H 11 NO2), 2-amino-1,5-phthalic acid, 3-amino-1,4-phthalic acid, 4-amino-1,4-phthalic acid, 2-amino-2-methylpropionic acid, 3-amino-2-ethylbutyric acid (C6H 13 NO2) or more, or none; the solvent is one or both of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO); the temperature A1 is 10-120°C, the stirring time T1 is 1-24h; the stirring speed B1 is 200rpm-800rpm.
[0032] Furthermore, in step 4,
[0033] The rotation speed B2 is 1000rpm-9000rpm, the time T2 is 10-200s; the temperature A2 is 30-200℃; and the time T3 is 1-30min.
[0034] Furthermore, in step 5,
[0035] The electron transport layer includes, but is not limited to, a single layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), lithium fluoride (LiF), zinc oxide (ZnO), titanium dioxide (TiO2), tin oxide (SnO2), etc. It can also be a double layer or multi-layer composed of several single electron transport layers; the rate I is The thickness i is 1-100 nm.
[0036] Furthermore, in step 6, the material of the top electrode noble metal layer includes but is not limited to noble metals such as gold, silver, and aluminum, and the rate J is The thickness j is 1-5nm, and the rate K is The thickness k is 5-80 nm.
[0037] Furthermore, in step 7,
[0038] The integration method of particles and devices includes but is not limited to dry transfer, direct liquid dripping and then drying with nitrogen, etc.; further, the materials of precious metal nanoparticles include but are not limited to gold, silver, platinum, palladium, rhodium, ruthenium, iridium, osmium, and other precious metal particles, which are not necessarily single-component, but can also be alloys of multiple components; the shapes of precious metal nanoparticles include but are not limited to spherical, cubic, cylindrical, needle-shaped, and irregular shapes, etc.; the structures of precious metal nanoparticles include but are not limited to solid, hollow, core-shell, multilayer structures, etc., and multilayer structures include but are not limited to the combination of metals and metals, and can also be the combination of metals and oxides such as SiO2 or other oxides. The size of precious metal nanoparticles is 30-5000nm.
[0039] Furthermore, the hole transport layer can be switched with the electron transport layer, with the electron transport layer adjacent to the bottom electrode and the hole transport layer adjacent to the top electrode.
[0040] The beneficial effects of the present invention are:
[0041] The present invention enhances the performance of perovskite LED (PeLED) based on precious metal nanostructures. Precious metal nanoparticles are sprinkled on the metal top electrode above the perovskite device, and the metal top electrode and the metal nanoparticles are combined to form a self-assembled antenna. The nanoantenna does not involve complex and delicate device manufacturing processes, and there is no material degradation. While retaining the primary performance of PeLED, it effectively reduces plasmon loss and enhances light output coupling in PeLED devices. It can synergistically improve the external quantum efficiency of PeLED devices, reduce the thermal aging effect caused by internal light loss, extend the life of the device, and improve the stability of the device. The light emission wavelength can be regulated by designing the device structure and utilizing plasmon resonance. A general method for enhancing light output coupling is provided, and the engineered PeLED nanostructure leaves considerable room, which is expected to have great potential in surpassing existing performance limitations. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a schematic diagram of the device structure of Example 1 in a method for enhancing the performance of perovskite LEDs based on precious metal nanostructures.
[0043] Figure 2 This is a schematic diagram of the device structure of Example 2 of a method for enhancing the performance of perovskite LEDs based on precious metal nanostructures.
[0044] Figure 3 Schematic diagram of noble metal nanoparticles of different shapes and structures in a method for enhancing the performance of perovskite LEDs based on noble metal nanostructures.
[0045] Figure 4Device structure diagram showing two different directions of holes and electrons in a method based on precious metal nanostructures to enhance the performance of perovskite LEDs. DETAILED DESCRIPTION
[0046] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0047] Embodiment 1:
[0048] This embodiment provides a method for enhancing the performance of green perovskite LED based on precious metal nanostructures. The device structure is Cr / Au / PEDOT:PSS / Perovskites / TPBi / LiF / Au. The particles selected are spherical gold nanoparticle core-shell structures. The device structure is as follows: Figure 1 The method specifically comprises the following steps:
[0049] Step 1: Depositing a bottom electrode using a thermal evaporation system;
[0050] Ordinary glass was cut into 1.5×1.5 cm pieces as the substrate, wiped clean with ethanol, and then ultrasonically cleaned with ultrapure water, acetone, and ethanol for 15 min each to clean the glass substrate, and then dried with nitrogen. After drying, a thermal evaporation system was used at a rate of A 5 nm thick adhesion layer chromium (Cr) film was evaporated and then A gold (Au) film with a thickness of 3 nm was evaporated, and then A gold (Au) film with a thickness of 77 nm was evaporated to serve as the bottom electrode.
[0051] Step 2, spin coating the hole transport layer using a spin coater;
[0052] The evaporated substrate was treated in a plasma cleaner for 15 min to enhance the surface hydrophilicity and remove organic impurities. Poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS) solution was spin-coated on the evaporated substrate at 4000 rpm in air for 50 s, and annealed at 150 °C in air for 15 min.
[0053] Step 3: Prepare the perovskite precursor solution in a nitrogen glove box (O2≤1ppm, H2O≤1ppm)
[0054] 0.2mmol lead bromide (PbBr2), 0.24mmol cesium bromide (CsBr), 0.08mmol phenethylammonium bromide (PEABr), and 0.028mmol dicyclohexane-18-crown-6 were dissolved in 1mL of dimethyl sulfoxide (DMSO), maintained at 30°C, and stirred at 500rpm for 12h. Then, the perovskite precursor solution was filtered through a 0.45μm polytetrafluoroethylene filter to obtain a clear and transparent precursor solution. Among them, lead bromide (PbBr2) is a lead halide, cesium bromide (CsBr) and phenethylammonium bromide (PEABr) are halide salts, and dicyclohexane-18-crown-6 is a small molecule additive.
[0055] Step 4, spin coating the perovskite film using a spin coater;
[0056] The substrate obtained in step 2 was also transferred to a nitrogen-filled glove box, and then the perovskite precursor solution prepared in step 3 was spin-coated on the hole transport layer film at a speed of 4000 rpm for 40 seconds, wherein the antisolvent (ether) was quickly dropped onto the surface after 20 seconds of spin coating. It was then placed on a heating plate and heated at 60°C for 5 minutes to obtain a perovskite film.
[0057] Step 5: Depositing an electron transport layer using a thermal evaporation system;
[0058] After the perovskite film is prepared, the substrate is transferred to a high vacuum deposition system (vacuum degree < 4 × 10 -4 Pa). Using the thermal evaporation method, a shadow mask is first used at a rate of 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was evaporated to a thickness of 40 nm; then, the film was evaporated at a rate of Lithium fluoride (LiF) was evaporated to a thickness of 1 nm.
[0059] Step 6: Depositing a metal top electrode using a thermal evaporation system;
[0060] After the electron transport layer is deposited, a noble metal gold (Au) layer is deposited using a shadow mask at a rate of Evaporate 3nm of precious metal gold (Au), then Noble metal gold (Au) was evaporated to a thickness of 12 nm as the top electrode.
[0061] Step 7: Integrate the noble metal nanoparticles with the perovskite LED using a dry transfer method;
[0062] In a nitrogen environment, a solution of gold nanoparticles was first evenly drop-coated onto the polydimethylsiloxane (PDMS) material and dried naturally; then, the side of the polydimethylsiloxane (PDMS) with the noble metal nanoparticles was adhered to the surface of the perovskite LED device (metal top electrode); finally, the polydimethylsiloxane (PDMS) was mechanically separated from the device.
[0063] Embodiment 2:
[0064] This embodiment provides a method for enhancing the performance of blue perovskite LED based on precious metal nanostructures. The device structure is Cr / Au / PVK / PVP / Perovskites / TPBi / LiF / Au. The particles selected are spherical gold nanoparticle core-shell structures. The device structure is as follows: Figure 2 The method specifically comprises the following steps:
[0065] Step 1: Depositing a bottom electrode using a thermal evaporation system;
[0066] Ordinary glass was cut into 1.5×1.5 cm pieces as the substrate, wiped clean with ethanol, and then ultrasonically cleaned with ultrapure water, acetone, and ethanol for 15 min each to clean the glass substrate, and dried with nitrogen. After drying, a thermal evaporation system was used at a rate of A 5 nm adhesion layer of chromium (Cr) film was evaporated and then A gold (Au) film with a thickness of 3 nm was evaporated, and then A gold (Au) film with a thickness of 77 nm was evaporated to serve as the bottom electrode.
[0067] Step 2, spin coating the hole transport layer using a spin coater;
[0068] The evaporated substrate was treated in a plasma cleaner for 15 min to enhance the surface hydrophilicity and remove organic impurities. Poly(9-vinylcarbazole) (PVK) was added at 6 mg ml -1 The poly(9-vinyl carbazole) (PVK) precursor solution was obtained by dissolving it in chlorobenzene at a concentration of 2 mg ml_, and then filtered through a 0.2 μm polytetrafluoroethylene membrane filter to obtain a poly(9-vinyl carbazole) (PVK) solution. The poly(9-vinyl carbazole) (PVK) solution was spin-coated onto the evaporated substrate at a speed of 5000 rpm in air for 40 s, and annealed at 100 °C in air for 15 min to deposit a poly(9-vinyl carbazole) (PVK) layer. The polyvinyl pyrrolidone (PVP) precursor solution was dissolved in chlorobenzene at a concentration of 2 mg ml_. -1Dissolved in isopropanol, filtered using a 0.45 μm polytetrafluoroethylene filter to obtain a polyvinyl pyrrolidone (PVP) solution, and then spin-coated the polyvinyl pyrrolidone (PVP) solution onto the poly (9-vinyl carbazole) (PVK) surface at a rotation speed of 5000 rpm in air for 20 s, followed by annealing at 100 ° C in air for 15 min to deposit a thin layer of polyvinyl pyrrolidone (PVP).
[0069] Step 3, preparing a perovskite precursor solution in a nitrogen glove box (O2≤1ppm, H2O≤1ppm);
[0070] 0.45mmol of lead chloride (PbCl2), 0.5mmol of lead bromide (PbBr2), 1.00mmol of cesium bromide (CsBr), 0.80mmol of p-FPEABr, 0.05mmol of formamidine bromide, 0.30mmol of lithium bromide, and 0.05mmol of zinc chloride were dissolved in dimethyl sulfoxide (DMSO), and the CsBr concentration was kept at 0.12M. The temperature was maintained at 45°C and stirred at a speed of 500rmp for 2h. The perovskite precursor solution was filtered through a 0.45μm polytetrafluoroethylene membrane filter to obtain a clear and transparent precursor solution.
[0071] Step 4, spin coating the perovskite film using a spin coater;
[0072] The substrate obtained in step 2 was also transferred to a nitrogen-filled glove box, and then the perovskite precursor solution prepared in step 3 was spin-coated on the hole transport layer film at a speed of 4500 rpm for 120 seconds. It was then placed on a heating plate and heated at 75°C for 5 minutes to obtain a perovskite film.
[0073] Step 5: Depositing an electron transport layer using a thermal evaporation system;
[0074] After the perovskite film is prepared, the substrate is transferred to a high vacuum deposition system (vacuum degree < 4 × 10 -4 Pa). Using the thermal evaporation method, a shadow mask is first used at a rate of 1,3,5-tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was evaporated to a thickness of 50 nm; then, the film was evaporated at a rate of Lithium fluoride (LiF) was evaporated to a thickness of 2 nm.
[0075] Step 6: Depositing a metal top electrode using a thermal evaporation system;
[0076] After the electron transport layer is deposited, a precious metal gold (Au) layer is deposited using a shadow mask by thermal evaporation at a rate of Evaporate 3nm of precious metal gold (Au), then Noble metal gold (Au) was evaporated to a thickness of 12 nm as the top electrode.
[0077] Step 7: Integrate the noble metal nanoparticles with the perovskite LED using a dry transfer method;
[0078] In a nitrogen environment, a solution of gold nanoparticles was first evenly drop-coated onto the polydimethylsiloxane (PDMS) material and dried naturally; then, the side of the polydimethylsiloxane (PDMS) with the noble metal nanoparticles was adhered to the surface of the perovskite LED device (metal top electrode); finally, the polydimethylsiloxane (PDMS) was mechanically separated from the device.
Claims
1. A method for enhancing the performance of perovskite LEDs based on precious metal nanostructures, characterized in that: The following steps are involved: Step 1: Depositing a bottom electrode using a thermal evaporation system; Step 2, spin coating the hole transport layer using a spin coater; Step 3, preparing a perovskite precursor solution in a nitrogen glove box; Step 4, spin coating the perovskite film using a spin coater; Step 5: Depositing an electron transport layer using a thermal evaporation system; Step 6: Depositing a metal top electrode using a thermal evaporation system; Step 7: Integrate precious metal nanoparticles with perovskite LEDs.